Pockets of Participation: Bureaucratic Incentives and Participatory Irrigation Management in Thailand - Jacob I. Ricks (Water Alternatives, 2015)
Despite a history of participatory policies, Thailand’s Royal Irrigation Department (RID) has had little success in developing water user organisations (WUOs) capable of facilitating cooperation between farmers and the irrigation agency. Even so, pockets of participation exist. What can explain these rare successes? What policy lessons can they provide? Comparing nine WUOs, I identify factors that contribute to the emergence of relatively successful groups. Most importantly, I show that successful WUOs are contingent on the actions of local irrigation officials. These findings emphasise the important role of street-level bureaucrats in implementing participatory policies. The incentive structures provided by the RID, though, deter most officials from sincerely collaborating and cooperating with farmers. Thus experts and policy-makers interested in promoting participatory resource management should focus more attention on shaping incentives for local officials to engage meaningfully with farmers.